Pengembangan Menu Kuliner Khas Berbahan Lele (Clarias SPP) untuk Meningkatkan Citra Desa Wisata Batu Kumbung - Ruwaida Fajriasanti; Harja, Oktomi; Anggara, A. A. Putu Gede Puja; Ahmadi, Lukman; Hidayatullah, Muhammad Adieb (LPPPM STAI Darul Hikmah Bangkalan, 2024)
Culinary and tourism are closely related. Culinary not only fulfills tourists' fundamental needs, but it also shapes the image of a tourism destination and provides tourists with an authentic and memorable experience. We carried out this Community Service (PKM) activity at Batu Kumbung Tourism Village, Lingsar District, West Lombok, NTB, with a primary focus on developing a culinary menu using local food ingredients. The local community chose catfish—especially the dumbo variety (Clarias spp.)—the village's leading commodity, as the main theme for the culinary specialties, aiming to enhance Batu Kumbung's image and competitiveness as a tourist village. PKM activities were carried out with a participatory approach through socialization, discussion, observation, interview, training, and practice methods. The community was actively involved in every participatory stage, from information gathering to consultation to empowerment. This way, the community can develop the knowledge and skills to create a specialty menu and apply good food processing techniques. The final product produced from this community service activity is a menu named “Dulang Lele Batu Kumbung,